GADGET TERHADAP PERKEMBANGAN ANAK PRA SEKOLAH: Gadget Terhadap Perkembangan Anak Pra Sekolah - Haerani, Mia; Qurrotua’ini, Hasna Aqiila; Ramdhan, Muhamad; Haryanto, Ricko Dwi (Ruang Ide Publisher, 2024)
Introduction: Etymologically, gadget is a term in English which means a small electronic device that has a special function. In Indonesian, gadgets are referred to as